Modeling of two-dimensional MoxW1−xS2ySe2(1−y) alloy band structure - N. Yu. Pimenov; S. D. Lavrov; A. V. Kudryavtsev; A. Yu. Avdizhiyan (Российский технологический журнал)
Objectives. Two-dimensional transition metal dichalcogenides (TMDs) are utilized for various optical applications due to the presence in these materials of a direct band gap corresponding to the visible and near-infrared spectral regions. However, a limited set of existing TMDs makes the region of the used spectral range discrete. The most effective way to solve this problem is to use two-dimensional TMD films based on multicomponent alloys, including three or more different chemical elements (while TMDs consist of two). By varying their morphological composition, one can control the value of the band gap and thus their optical absorption spectrum. However, since the band gap in such structures is highly nonlinear as far as their chemical composition is concerned, it can be challenging to select the required concentration in order to achieve uniform absorption. In this regard, the purpose of this work is to theoretically determine the dependence of the band gap of four-component two-dimensional MoxW1–xS2ySe2(1–y) alloys on their morphological composition.Methods. The calculations were performed within the framework of the density functional theory using the Quantum Espresso software package. Flakes of two-dimensional TMDs alloys were prepared from bulk TMDs crystals by mechanical exfoliation on a Si/SiO2 substrate. An experimental study of the photoluminescence characteristics was carried out using photoluminescence microscopy-spectroscopy. Results. In this work, the dependence of the band gap on the morphological composition of two-dimensional MoxW1–xS2ySe2(1–y) alloys was determined. Upon varying the composition of TMDs alloys, it was found that the band gap changes from 1.43 to 1.83 eV. The obtained theoretical results are in qualitative agreement with the experimental data.Conclusions. The minimum band gap is observed in alloys close to MoSe2, while alloys close to WS2 have the maximum band gap value.